2002
DOI: 10.1088/0953-8984/14/18/307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microstructure on the magnetic and mechanical behaviour of amorphous and nanocrystalline FeNbB alloy

Abstract: The formation of a nanocrystalline structure and its influence on the magnetic and mechanical properties in a ternary Fe 80.5 Nb 7 B 12.5 alloy has been investigated using a variety of complementary methods. The crystallization studies performed by DSC calorimetry, magnetization and electrical resistivity measurements have confirmed a two-stage nature of the primary crystallization process. The microstructure in the series of heat-treated amorphous and nanocrystalline specimens with different volume fractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…The spectra were recorded between 300 K and 77 K using both a bath cryostat and a homemade cryofurnace, in which the sample under helium atmosphere and secondary vacuum (10 -6 Torr), respectively, can be well thermalised (indeed, the instrumental design of the cryofurnace prevents from temperature deviations of the sample) [41][42][43][44][45][46] . In-field Mössbauer experiments were carried out using a cryomagnetic device where the applied field is oriented parallel to the -beam, the sample located in the main coil and the source in the compensated coil, preventing thus from polarization effects.…”
Section: Methodsmentioning
confidence: 99%
“…The spectra were recorded between 300 K and 77 K using both a bath cryostat and a homemade cryofurnace, in which the sample under helium atmosphere and secondary vacuum (10 -6 Torr), respectively, can be well thermalised (indeed, the instrumental design of the cryofurnace prevents from temperature deviations of the sample) [41][42][43][44][45][46] . In-field Mössbauer experiments were carried out using a cryomagnetic device where the applied field is oriented parallel to the -beam, the sample located in the main coil and the source in the compensated coil, preventing thus from polarization effects.…”
Section: Methodsmentioning
confidence: 99%
“…This material belongs to the group of the Fe-M-B-(Cu) alloys (M=Zr, Hf and Nb), called also NANOPERM. The particular interest in these alloys results from their excellent soft magnetic properties [3], which make them promising candidates for various soft magnetic applications. In spite of a large number of research activities on different aspects of magnetism in the NANOPERM alloys, they magnetocaloric properties remain fairly unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Pieces of these ribbons were annealed under protective argon atmosphere for 1 hour at temperatures 743, 783 and 883 K in order to prepare the set of nanocrystalline samples characterized by different microstructure. A previous detailed structural characterization [10,11] has revealed that the sample annealed at 743 K for 1 hour represents an example of nanocrystalline system with a low fraction of bcc-Fe crystalline grains, the sample annealed at 783 K for 1 hour corresponds to the material in a medium stage of primary crystallization process and the sample annealed at 883 K for 1 hour represents a stage, where the primary crystallization process is nearly finished. The mean grain sizes that correspond to these different annealing stages are <8 nm, 10-14 nm and 15-20 nm, respectively.…”
mentioning
confidence: 99%